Choroidal neovascularization in Bardet-Biedl syndrome. (June 2013) - Charkoudian, Leon D.; Barañano, David E.; Fortun, Jorge; Yan, Jiong; Srivastava, Sunil K.
<x xml:space="preserve">Abstract</x> Purpose: To describe a case of choroidal neovascularization in a young patient with genetically-proven Bardet-Biedl syndrome. Methods: Case description with fundus and anatomical photography and optical coherence tomography. Patients: Single patient case description. Results: Fundus photography and optical coherence tomography reveal the presence of previously-active choroidal neovascularization. Anatomical, historical, and genetic evidence confirm Bardet-Biedl syndrome in this individual. Discussion: Choroidal neovascularization accompanying this syndrome has not been reported. Herein we describe the first published description of choroidal neovascularization in an individual with genetically-proven Bardet-Biedl syndrome.